(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate the clinical characteristics of melasma and to evaluate the effectiveness of Almariderm Vero Melascreen in the treatment of melasma among patients at Ca Mau Eye–Dermatology Hospital in 2024–2025.Methods: This was an interventional study with prospective longitudinal follow-up, conducted on 36 patients diagnosed with melasma who presented to Ca Mau Eye–Dermatology Hospital in 2024 and 2025. Descriptive and analytical statistical methods were applied, along with appropriate statistical tests. Statistical significance was set at p < 0.05. Results: The mean melasma area and severity index (MASI) score after treatment with Almariderm Vero Melascreen decreased markedly from 13.4 ± 3.9 (n = 36) at baseline to 7.3 ± 2.5 (n = 36) after 12 weeks of treatment. The severity of melasma showed substantial improvement compared with baseline, with the proportion of patients with severe and very severe melasma decreasing by more than 60.0% after treatment. Transient adverse effects were mild and included slight burning sensation (8.3%) and mild erythema (5.6%). Conclusions: Treatment of facial melasma with Almariderm Vero Melascreen is an effective and safe therapeutic option. However, a relatively prolonged treatment duration is required.